What is the underlying structure of the climate, conflict, and socio-economic system in Sudan? A network analysis - Basel, Ashleigh Megan; Onivola Minoarivelo, Henintsoa; Craparo, Alessandro Carmelo William; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet gives answers on how climate exacerbates root causes of conflict in Sudan, using network analysis. Results show that the base of the Sudanese network is underpinned by pastoralist society and agricultural productivity. Increased evapotranspiration, has direct impacts on net primary production.